Effects of crystallization and bubble nucleation on the seismic properties of magmas. (28th February 2016) - Tripoli, Barbara Andrea; Cordonnier, Benoit; Zappone, Alba; Ulmer, Peter
Abstract: Seismic tomography of potentially hazardous volcanoes is a prime tool to assess the location and dimensions of magmatic reservoirs. Seismic velocities are strongly affected by processes occurring within the conduit or in the magma chamber, such as crystallization and bubble exsolution. However, the limited number of constrained measurements does not allow yet to link seismic tomography and the textural state of a particular volcanic system. In this study, we investigated a chemically simplified melt in the system CaO‐Na2 O‐Al2 O3 ‐SiO2 ‐H2 O‐CO2, which undergoes plagioclase crystallization and bubble exsolution. A Paterson‐type internally heated gas pressure apparatus was employed to measure ultrasonic velocities at a constant pressure of 250 MPa and at temperature from 850 to 700°C. Magmatic processes such as crystallization, bubble nucleation, and coalescence have been recognized throughout the measurements of seismic velocities in the laboratory. Compression and shear wave velocities increase nonlinearly during crystallization. At a crystal fraction exceeding 0.45, the formation of a crystal network favors the propagation of seismic waves through magmatic liquids. However, bubble nucleation induced by crystallization leads to an increase of magma compressibility resulting in a lowering of the wave propagation velocities. These two processes occur simultaneously and have a competing influence on the seismic properties of magmas. In addition, as already observed by previous authors, when the bubble fraction is less than 0.10, the decrease in seismic velocities is more pronounced than for higher bubble fractions. The effect of bubble coalescence on elastic properties is thus lower than the effect of bubble nucleation. Key Points: Magmatic processes are identified through the laboratory measurement of seismic velocities Seismic velocities increase nonlinearly during crystallization Bubble nucleation induces larger decrease in Vp and Vs than bubble coalescence